A Feasibility study on ERI Silk Production - Del Rosario, Ryan Kenneth F.; Gonzalez, Noelle H.; Santos, Pamela M. (Diliman, Quezon City College of Engineering, 2004)
The project aims to introduce the eri silk industry in the Philippines and establish a business center catering the breeding and raising of eri silk worms. To achieve this, the project needs to develop the local eri silk demand and support the downstream production industries. The business center will need initial capital infusion, site and equipment identification and preparation, and estimates of expenses and income levels. A ten-year study time frame is deemed suitable for investment purposes but the actual project life span is predicted to be much longer. Prevailing market prices were used in the financial estimates with labor compensation being set at par or above industry levels. The project took into consideration existing policies and regulations of the country, while determining the best organizational set-up and initial source of capital to operate profitably. The primary data inputs were gathered from government institutions such as the National Statistics Office, the Bureau of Investments, Philippine Textile Research Industry, and Department of Science and Technology. The market study was generated using 3 Period Moving Average, 3 Period Weighted Moving Average and Linear Regression forecasting. The marketing strategy was formulated in view of the customs and tradition practiced by the local people. Numerous sources from abroad were sifted to obtain the wide range of possible technical alternatives. From these, the most compatible and most appropriate production methodology was designed. The financial statements were drafted using inputs from the market and technical study. The location has been identified as a 20-hectare rural area in Baguey, Cagayan. The processes were chosen to ensure the least environmental disturbance while attaining high yield in response to production objectives. The overall production strategy is designed to be compatible with the Philippine setting. Initial capitalization will come from (%) debt and (%) equity financing. The financial strategy prioritized early debt relief as opposed to early profitability. The numerous advantages of the project outlined in the feasibility study are clear indicators that the project is advantageous to the country and the government, and should be pursued immediately.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Exotic Ricini Incorporated (ER Inc.); Silk industry; Participatory monitoring and evaluation (Project management)